2018
DOI: 10.1038/s41598-018-25467-9
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Exposure and Mortality from Cardiovascular Disease and Cancer in Early NASA Astronauts

Abstract: Understanding space radiation health effects is critical due to potential increased morbidity and mortality following spaceflight. We evaluated whether there is evidence for excess cardiovascular disease or cancer mortality in early NASA astronauts and if a correlation exists between space radiation exposure and mortality. Astronauts selected from 1959–1969 were included and followed until death or February 2017, with 39 of 73 individuals still alive at that time. Calculated standardized mortality rates for te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 36 publications
1
42
0
2
Order By: Relevance
“…25 Consistent with this hypothesis, prior studies of cardiovascular disease among astronauts show reductions in both incidence and mortality in comparison to the general population. [4][5]26 Large differences in incidence and mortality rates between a largely never-smoker population and the US population as shown in table 4 are to be expected. However, due to changing smoking patterns in the US population over time, determining whether this difference in lung cancer is entirely due to healthy behavior or whether space ight exposures are contributing to a cancer risk would require a more detailed analysis.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…25 Consistent with this hypothesis, prior studies of cardiovascular disease among astronauts show reductions in both incidence and mortality in comparison to the general population. [4][5]26 Large differences in incidence and mortality rates between a largely never-smoker population and the US population as shown in table 4 are to be expected. However, due to changing smoking patterns in the US population over time, determining whether this difference in lung cancer is entirely due to healthy behavior or whether space ight exposures are contributing to a cancer risk would require a more detailed analysis.…”
Section: Discussionmentioning
confidence: 96%
“…3 A study of astronauts selected before 1970, with follow-up through February 2017, also reported astronauts to be at less than half the risk of death from all cancers in comparison to the general population. 4 Within the full cohort and with follow-up through October 2017, astronauts were reported to be at only 62% the risk of the general population for mortality from all cancers (95% CI = 37-97%). 5 Finally, in comparison to professional basketball players, astronauts were at no differential risk of cancer mortality, with only a nominal and non-signi cant 10% lower mortality rate for astronauts.…”
Section: Introductionmentioning
confidence: 98%
“…This confounds epidemiological analyses, making it difficult to detect significant differences from background disease without a large study population 34 . This issue is especially significant in astronaut cohorts because those studies have small sample sizes 35 . There is also a general lack of experimental data that specifically addresses the role of radiation at low, space-relevant doses 36 .…”
Section: Space Radiation Health Risksmentioning
confidence: 99%
“…However, scrutiny into the health of the 24 Apollo lunar astronauts has highlighted increased mortality from cardiovascular disease when compared to astronauts from both low-Earth orbit and those who have never taken part in space flight [4] . These differences may be accounted for by higher levels of exposure to components of galactic cosmic rays and solar particle events outside the Earth’s protective magnetosphere [5] . Consequently, focus has heavily accentuated upon the acclimatization and safety of astronauts on future enduring missions.…”
Section: Introductionmentioning
confidence: 99%